To bean or not to bean : a study about farmers’ resources and their decision to grow broad beans - Månsson, Emil; Öhlin, Jenny (SLU/Dept. of Economics, 2019)
Climate change and sustainability is discussed all over the world. In Sweden, as well as in many other countries worldwide, the food and agricultural system is one of the most important industries. It is both affected by and affecting climate change. Modern agricultural production relies on an increasingly higher use of resources and inputs to maintain a high production level of animal feed and human food. Expansion of legumes could improve resource efficiency and promote diversification of cropping systems which leads to a more sustainable agriculture. Despite all of the potential and benefits of growing more legumes, less than 2 % of the acreage in Sweden was used for legume production in 2018. Broad bean is one of the legumes that can be grown in large parts of Sweden and would be relatively easy to start growing.